Identifikasi Citra Penyakit Mata Katarak Menggunakan Convolutional Neural Network - Bu'ulolo, Geza Jeremia; Jacobus, Agustinus; Kambey, Feisy Diane (Universitas Sam Ratulangi, 2021)
Convolutional Neural Network architecture is part of deep learning. In this architecture has a biological process that has a pattern of connectivity between neurons resembling the visual cortex. In the output of this architecture in the form of predictions for identification in an image of a cataract eye and an image of a normal eye. Based on testing of the system on a web-based application, the system that was built succeeded in identifying cataract eye images and normal eye images with test data as much as 30% of the training data. From the tests carried out on parameter values and tests on the optimizer on the Convolutional Neural Network architecture method, the accuracy results with an average of 96.8% on the RMSProp optimizer, 94.5% on the Adam optimizer, 74.5% on the SGD optimizer, and 63.5% on the AdaDelta optimizer.Arsitektur Convolutional Neural Network merupakan bagian dari deep learning. Dalam arsitektur ini memiliki proses biologi yang memiliki pola konektivitas antar neurons menyerupai korteks visual.Â Dalam hasil keluaran dari arsitektur ini berupa prediksi untuk identifikasi pada suatu citra mata katarak maupun citra mata normal. Berdasarkan pengujian terhadap sistem pada aplikasi berbasis web, sistem yang dibangun berhasil mengidentifikasi citra mata katarak dan citra mata normal dengan data uji sebanyak 30% dari data pelatihan. Dari pengujian yang dilakukan terhadap nilai parameter dan pengujian terhadap optimizer pada metode arsitektur Convolutional Neural Network mendapatkan hasil akurasi dengan rata-rata adalah 95% pada optimizer RMSProp, 94,5% pada optimizer Adam, 74,5% pada optimizer SGD, dan 63.5% pada optimizer AdaDelta.